REKONSTRUKSI TERHADAP SIFAT FINAL DAN MENGIKAT DALAM PUTUSAN MAHKAMAH KONSTITUSI - R. Nurman Ardian A.K.; Muhammad Akib; Budiyono Budiyono (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
AbstractCourt verdict of District Heads Election is the first verdict and the last hadfinal and binding since it was read out by Constitutional Court, although itfound and generated by the corruption court, so it unfulfilled sense of justiceas corruption of the judiciary in the dispute over the elections involving AkilMukhtar. Finding a model for retesting on the Court's Verdict in strictHeads Election disputes that did not fulfill justice was a goal to be achieved.This paper used juridicial normative methods. The conclusion of this paperthat for guarantee the legal certainty, the Constitutional Court verdictremains final and binding, but it can be applied to reopen the trial bymechanism “constitutional complaint” as the law of justice fulfillment, inaddition, the presence of amicus curiae through the amicus brief and theexamination of the judgment can serve as a model of the fulfillment of justicethat has been closed. In order for such efforts to be implemented, it isadvisable to regulate such terms or conditions through the amendment of theConstitutional Court Law and / or by the verdict of the Constitutional Courtas a precedent (judge made law) which is subsequently elaborated throughthe Constitutional Court Regulations.Keywords: Verdict, Constitutional Court, Reconstruction.AbstrakPutusan perkara Pilkada merupakan putusan pertama dan terakhir yangmengikat umum sejak dibacakan Mahkamah Konstitusi, meskipun terdapatdan dihasilkan oleh peradilan sesat sehingga tidak terpenuhi rasa keadilansebagaimana terjadi korupsi peradilan dalam sengketa hasil Pilkada yangmelibatkan Akil Mukhtar. Menemukan model pengujian kembali terhadapputusan Mahkamah dalam sengketa Pilkada yang tidak memenuhi keadilanmerupakan tujuan yang hendak dicapai. Menggunakan pendekatan yuridisnormatif dapat disimpulkan bahwa guna menjamin kepastian hukum,putusan Mahkamah Konstitusi tetap bersifat final dan mengikat, tetapi dapatdilakukan permohonan untuk membuka kembali persidangan denganmekanisme constitutional complaint sebagai upaya hukum pemenuhankeadilan, selain itu, kehadiran amicus curiae melalui amicus brief sertaeksaminasi terhadap putusan dapat dijadikan sebagai model pemenuhankeadilan yang sudah tertutup. Agar upaya tersebut dapat dilaksanakan,disarankan mengatur syarat-syarat atau ketentuan dimaksud melaluiperubahan Undang-undang Mahkamah Konstitusi dan/atau dengan putusanMahkamah Konstitusi sebagai preseden (judge made law) yang kemudiandiperinci melalui Peraturan Mahkamah Konstitusi.Kata kunci: Putusan, Mahkamah Konstitusi, dan Rekonstruksi